MIKROENKAPSULASI EKSTRAK BUAH BUNI (Antidesma bunius L.) MENGGUNAKAN MALTODEKSTRIN DENGAN METODE SPRAY DRYING - Michrun Nisa; Agustina Ma'tang Parinding; Abdul Halim Umar; Nur Khairi; Astuti Amin; Maulita Indrisari; Wahyu Hendrarti; Andi Nur Aisyah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Buni fruits (Antidesma bunius L.) is one of the plants that contain anthocyanin dyes. This study aims to create and characterize buni fruit extract microcapsules containing anthocyanin using spray drying method. The coating materials used were 5%, 7%, 5%, 5%, and 5% of the maltodextrin. Buni fruit was determined by the total content of anthocyanin and microcapsules obtained by organoleptic characterization, microencapsulation efficiency, particle morphology, and particle size distribution. The total content of anthocyanin from buni fruit extract is 18.14 mg/100g. Microcapsules obtained by variation concentration of pink maltodextrin typical of buni fruit weighing 2.7 g, 3.3 g, 2.3 g, obtained the value of EEC (%) 50, 55, and 59, respectively, on the appearance of SEM form spheries and on PSA particle size distribution 2.5 Î¼m, 2.1 Î¼m, 2.6 Î¼m.